Profit shifting and tax‐rate uncertainty. (4th February 2020) - Delis, Manthos D.; Hasan, Iftekhar; Karavitis, Panagiotis I.
Abstract: Using firm‐level data for 1, 084 parent firms in 24 countries and for 9, 497 subsidiaries in 54 countries, we show that tax‐motivated profit shifting is larger among subsidiaries in countries that have stable corporate tax rates over time. Our findings further suggest that firms move away from transfer pricing and toward intragroup debt shifting that has lower adjustment costs. Our results are robust to several identification methods and respecifications, and they highlight the important role of tax‐rate uncertainty in the profit‐shifting decision while pointing to an adjustment away from more costly transfer pricing and toward debt shifting.